The Art of Mosque Calligraphy and its Development in Indonesia - Siti Chairun Nisyah; Fauziah Nur; Irwansyah Jul Nasution; Sholihah Titin Sumanti; Haidar Putra Daulay (LPPM UIKA Bogor, 2024)
Known as khat, or the art of beautiful writing, calligraphy is one type of Islamic art that has gained popularity among Muslims. These beautiful carvings serve as a reminder of God’s existence and a display of beauty. The history of the development of Islamic calligraphy art from the time of Daulah Bani Umayyah to its development in Indonesia is the main topic of the research. The research uses descriptive qualitative analysis, namely the library esearch method. The results of the discussion show that the development of Islamic calligraphy art actually began since the time of the Prophet and Khulafaur Rasyidin, continuing through the Umayyad, Abbasid, and Post-Abbasid periods. During its development, various styles of writing or khat emerged. In Indonesia, the art of Islamic calligraphy has developed through a long journey, involving the Pioneer Force, the Pesantren Force, the Painter and Breaker Force, and the MTQ (Musabaqah Tilawatil Qur’an) Cadre Force.